Vocabulary acquisition through a subtitled movie clip among university students of UiTM Melaka / Noor Alina Namami - Namami, Noor Alina (2011)
This study is to examine whether the use of standard subtitles helps second language learners to acquire new vocabulary in the target language significantly in Malaysian context. Additionally, this research was conducted to study the differences between watching movie clip with subtitles, and movie clip with no subtitles among second language university students and their rates of vocabulary acquisition. The research design was a quasi- experimental design, which used the Wesche & Paribakht’s (1996) Vocabulary Knowledge Scale (VKS) in order to measure the rates of vocabulary acquisition of the participants before and after they have watched the movie clip provided. The independent variable for this study was the movie clip and the subtitles, whereas, the dependent variable would be the rates of acquisition of the participants. Data obtained from the study were analysed using the descriptive statistics in SPSS Version 17 in comparing the means concerning to address the first research question. For the second research question, the researcher used One Sample T-test to compare the gains and the difference between control and treatment group, and Paired Samples T-test to measure the significance difference between control and treatment group. The findings of this study revealed that the treatment group gained slightly better in terms of vocabulary acquisition as compared to the control group that had watched the movie clip with no subtitles. Moreover, the relationship between the subtitles and the rates of acquisition was found significant for the Treatment group and Control group also showed improvement during the post-test though it is not significant. Pedagogical implications are offered along with suggestions for further research.